Application of hydroxypropylated crosslinked starch from the grains of Oryza sativa L. as potential disintegrant in compressed solid dosage form. - Elizabeth A. Pagtalunan; Judson Lowie T. Ramos; Gerard Q. De Guzman (GarVal Editorial Ltda., 2022)
Context: The modification of starch from the grains of NSICRc222 rice variety may provide a new material with enhanced disintegrating functionality in compressed solid dosage forms. Aims: To synthesize hydroxypropylated crosslinked rice starch that may possess characteristics of a good disintegrant. Methods: Starch was isolated by the wet milling method. The crosslinking was performed using trisodium trimetaphosphate as crosslinking agent, and successively hydroxypropylated by using phosphorous oxychloride. The evidences of chemical modifications were determined by FTIR, TGA, and DSC. The application of modified rice starch as a disintegrant was evaluated by determining the dissolution profile, and was compared to the performance of commercially available disintegrants. The compatibility of modified rice starch was employed using FTIR, and the stability of the formulation was subjected to an accelerated stability study. Results: The changes in infrared spectra and thermogram confirmed successful chemical modification of rice starch. Allopurinol and modified starch mixture staged from 0 to 3 months showed no significant changes in the infrared spectra, which suggest compatibility of HCR with allopurinol. The dissolution rate of allopurinol tablets at pH 1.2, pH 4.5, and pH 6.8 with various superdisintegrants were comparable to the dissolution rate that utilized hydroxypropylated crosslinked rice starch as disintegrant. The accelerated stability study showed no significant changes from 0th to 3rd month, and no degradation products were detected in the HPLC analysis. Conclusions: The chemical modification of rice starch through crosslinking and hydroxypropylation yielded a novel material comparable to the commercially available superdisintegrants.